Penetapan Biaya Upah Petani Jagung dalam Konsep Huyula: Studi Kasus di Desa Bukit Aren - Gita Febriani Panigoro, Gita Febriani Panigoro; Mattoasi, Mattoasi; Siti Pratiwi Husain, Siti Pratiwi Husain (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research departs from the phenomenon of wage-wage practices that occur in Bukit Aren Village using the local community's traditional system, namely the mutual cooperation system or in Gorontalo language known as "Huyula". Determining employee wage rates for each job is important because employees expect service rewards from the results of their work. Determining appropriate wage rates will have an impact on employee work results in accordance with the agreed provisions. This research is related to Management Accounting with the concept of determining employee/farmer wage rates using the Huyula concept in Bukit Aren Village. The method used to answer this research phenomenon is using qualitative methods and using researchers as the main instrument for several data sources, both document data and interview data. The research results show that the determination of wage rates using the Huyula concept is carried out by means of mutual remuneration for corn farmers. This determination is based on a tradition of mutual cooperation or commonly known as Huyula by corn farmers in Bukit Aren Village where the wages received by corn farmers are based on a work practice with the Huyula system or mutual cooperation where this practice is a work system that helps each other work in shifts or a system of labor exchange relationships. The land owner only provides food without wages, because the next day a system like this is a reciprocity between the two parties if the other party will carry out farming activities.